Cork for sustainable product design - Mestre, Ana (2011)
Sustainable Product Design is currently accepted as one of the most promising trends in the “Sustainable Development” movement. It is often seen as a facilitation tool to implement Sustainability in practice, by improving the life cycle and eco-efficiency of products, by promoting dematerialization and by proposing completely new innovative sustainable solutions, services and products which encourage and communicate new “Sustainable Life Styles and Scenarios” and that can both stimulate the economic competitiveness of local industries and promote a more sustainable consumption [1]. In this context cork, a natural, recyclable, non-toxic, renewable resource, with outstanding environmental qualities, incorporating a high potential of innovative technological characteristics, can play a relevant role. Cork is a versatile raw material which adopts different technological transformation processes which can be used in different applications. Among the most noteworthy groups of cork materials available on the market are natural cork, granulates, composite agglomerates and expanded agglomerates. In addition, extensive ranges of new composite agglomerates have been patented and are at the implementation stage. This article presents an overview of: 1) the environmental, social and economic aspects of cork; 2) the cork materials, processes and technologies including a portfolio of cork materials available for sustainable product design; 3) a reflection about the current cork applications along with a discussion centred on the gap between the research and development of cork materials and its application in new products. The article concludes by stating that cork offers industrial designers a number of product-technology options that can generate potentially new sustainable product design solutions not yet tested on the market